Vivienne Westwood : The Journey to Establishing and Communicating Brand Value - Jakubovszkaja, Daria; Pospíšil, Jan, 1983-; Šimůnek, Michal, 1976-; Vysoká škola ekonomická v Praze. Fakulta managementu (2025)
This bachelor thesis investigates how Vivienne Westwood communicates and rein-forces brand value in the digital era by analysing five years (2018-2023) of Instagram and Facebook activity. Drawing on cultural-branding and value-co-creation theory, the study employs qualitative content, thematic and sentiment analysis, supported by engagement metrics, to decode posts and their audience reactions.
Vedoucí práce: Jan Pospíšil
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta managementu
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: management [obor bakal. práce]; bakalářské práce; bachelor's theses